Systematic Review of Efficacy of Interventions for Social Isolation of Older Adults - Tong, Feng; Yu, ChengLin; Wang, LinSen; Chi, Iris; Fu, Fang (Frontiers in Psychology, 2021)
Background：The social isolation of older people is a growing public health concern. The proportion of older people in society has increased in recent decades, and it is estimated that approximately 40% of the population will be aged 50 or above within the next few decades. This systematic review aims to summarize and renew knowledge of the effectiveness of existing interventions for alleviating social isolation of older adults. Methods：Relevant electronic databases, including Cochrane Library, CINAHL, SCOPUS, and Web of Science were searched by a systematic evaluation method. Eligible Randomized Controlled Trail (RCT) studies were published between 1978 and 2021 in English or Chinese. The primary and secondary outcomes were social isolation and loneliness. The quality of the included RCTs was scored by the Cochrane Risk of Bias Tool to assess their quality. Two independent reviewers extracted data using a standardized form. Narrative synthesis and vote-counting methods were used to summarize and interpret study data. Results：Twenty-four RCTs were finally included in this review. There was evidence of substantial heterogeneity in the interventions delivered. The overall quality of included studies indicated a low to medium risk of bias. Eighteen of twenty-four RCTs showed at least one dimension effect on reducing social isolation. The interventions with accurate targeting of clients in social and public places had more obvious effect. The Interventions in which older people are active participants also appeared more likely to be effective. In addition, group intervention activities and individual intervention interviews were effective in improving structural social support; mixed intervention and group intervention on training support significantly improved functional social support. Conclusions: This study suggests that group and mixed intervention targeting of older adults could be helpful for alleviating social isolation problems. The use of modern technology for remote services could also present good results. More well-conducted RCTs of the effectiveness of social interventions for alleviating social isolation are needed to improve the evidence base. Especially as the debating results on remote interventions, further research in this field should be conducted.